2018
DOI: 10.1080/14786419.2018.1460835
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the extraction of bioactive molecules from Lycium barbarum fruits and evaluation of the antioxidant activity: a combined study

Abstract: Novel food, super food, wolfberry, the Himalayan longevity fruit. Several different and, even more, colourful names define the fruits of Lycium barbarum L., one of the most popular food supplements and anti-aging remedies of the recent years. Goji derivatives find application at the interface between food and medicine thanks to the claimed antioxidant and immunomodulatory properties. Aiming at identifying the most effective extraction protocol for processing different goji berries samples (fresh and dried, com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…Goji berries were chosen for testing because recent studies have shown that their extracts possess biological activities, including anti-aging, anti-cancer, immunomodulatory and cytoprotective [10]. Studies conducted by Lin et al revealed that an aqueous Lycium barbarum extract increased phagocytic activity of mouse macrophages cell line RAW 264., as well as stimulated the production of cytokines and nitrogen oxide [11].…”
Section: Introductionmentioning
confidence: 99%
“…Goji berries were chosen for testing because recent studies have shown that their extracts possess biological activities, including anti-aging, anti-cancer, immunomodulatory and cytoprotective [10]. Studies conducted by Lin et al revealed that an aqueous Lycium barbarum extract increased phagocytic activity of mouse macrophages cell line RAW 264., as well as stimulated the production of cytokines and nitrogen oxide [11].…”
Section: Introductionmentioning
confidence: 99%
“…The presence of several mechanisms is perfectly in harmony with the growing interest towards the development of multi-target-directed ligands (MTDL) that take advantage of synergistic pharmacological effects [62]. Moreover, depending on their chemical structures, the neuroprotective effect of several natural and nature-inspired compounds, as outlined above, is also connected with their activity against reactive oxygen species (ROS) and inflammation [63][64][65][66]. In this connection, it was also reported that natural PDE in-hibitors, by increasing cGMP levels, reduce the production of IL-6 and TNF-α [23].…”
Section: Conclusion: the Perspective Of The Medicinal Chemistmentioning
confidence: 95%
“…Several classes of approved drugs have been studied through the years for their antioxidant properties [ 1 , 5 , 6 ]. Proton pump inhibitors [ 7 ], antidiabetics [ 8 ], drugs acting on the cardiovascular system [ 9 ], antiepileptics [ 10 ], and anti-inflammatory agents [ 11 ] represent some of the investigated classes, which are also paired by antioxidant natural and semi-synthetic compounds with biological activity [ 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ]. Furthermore, besides therapeutic agents, it must be stressed that bioactive components from diet have been recognized among the risk factors or, on the other hand, protective agents possibly influencing oxidative stress and pathogenesis of related diseases [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Scheme 3. N-acetyl cysteine (8), rutin(9), melatonin (10), hydroxytyrosol(11), caffeic acid phenethyl ester(12), resveratrol(13), quercetin(14), lycopene(15), apocynin(16) and ebselen(17).…”
mentioning
confidence: 99%